Mobile Ocean Bottom Seismometer Instrument (MOBSI) data from Arctic rivers, lakes, and seas - Angelopoulos, Michael; Ryberg, Trond; Rasmussen, Christian; Haberland, Christian; Juhls, Bennet; Dallimore, Scott; Boike, Julia; Overduin, Pier Paul (Zenodo, 2023)
We collected the data using the Mobile Ocean Bottom Seismic Instrument (MOBSI). The MOBSI is portable (9 kg) and consists of a watertight, heavy-duty pressure housing (diameter 30 cm, height 35 cm) containing a three-component, broadband seismic sensor. There are three channels (two horizontal and one vertical) recorded by the built-in data logger to monitor ambient seismic noise. Deployed by a steel cable from a small boat or zodiac, the device was lowered to the bottom of the water bodies or the top of the beach area (if present). The device recorded ambient seismic noise for a few minutes before being retrieved and moved to a new location. The steel cable was outfitted with a communications cable, which allowed for live data analysis and quality control via a shipboard monitor. This ensured that the tilt of the instrument was correct (less than 5 degrees) and that the deployment time was sufficient. We stopped data collection when the "real-time" H/V ratio was stable, i.e., not changing with time. For all soundings, the sampling frequency was set to 100 samples per second. The MOBSI data was recorded in an internal RAW format that was converted to MINISeed format. In this paper, we present MOBSI data for seven survey lines from the Russian and the Canadian Arctic. The Banja Lake and Lena River profiles are situated in the Lena Delta, northeastern Siberia, Russia. Ivashkina Lagoon is located along the southern coastline of the Bykovsky Peninsula, northeastern Siberia, Russia. The Tuktoyaktuk profiles are located north of Tuktoyaktuk Island (Northwest Territories, Canada) in the Canadian Beaufort Sea. The survey lines presented in this manuscript are the following: Profile A-A' (Banja Lake): 8 soundings Profile B-B' (Banja Lake): 9 soundings Profile C-C' (Banja Lake): 9 soundings Profile D-D' (Lena River-Samoylov Island): 9 soundings Profile E-E' (Lena River-Chay-Tumus): 16 soundings Profile F-F' (Tuktoyaktuk Island): 10 soundings Profile G-G' (Tuktoyaktuk Island): 9 soundings Profile H-H' (Ivashkina Lagoon): ...